Il cinema di Pasolini e la morte: tra complesso della mummia e sindrome di Frankenstein (Altre Modernità, 2010)
Cinema's ability to defeat death by stopping the run of time is written inside its own statute. Confiding on this capacity, Pasolini devotes his filmic work to the theme of death (interrogated through Christ's myth) and elaborates a linguistic theory (strictly linked to the performative aspects of his artistic work) to give an explanation of death through a filmic metaphor.